Emotional alterations in idiopathic Parkinson's disease without dementia (2017)
Currently Parkinson’s disease (PD) is no longer considered a disease exclusively motor type, now PD is characterized as cognitive neurobehavioral pathology often results in patients emotional disturbances that degrade their quality of life.